Benefits and challenges of cancer peer support groups: A systematic review of qualitative studies - Jablotschkin, Martina; Binkowski, Lena; Markovits Hoopii, René; Weis, Joachim (European journal of cancer care, 2022)
Introduction Although cancer self‐help groups (CSHGs) have increased in importance in recent years, certain aspects have not yet been sufficiently investigated in studies to date. In particular, little is known about members' experiences in face‐to‐face peer led CSHGs. This systematic review aims to synthesise qualitative studies documenting personal experiences of CSHG members and to enlighten group processes and mechanisms. It focuses on benefits and challenges of participating in face‐to‐face CSHGs in studies based on qualitative research. Methods MEDLINE, PsycINFO and PSYNDEX were used to identify relevant studies published from January 2000 to April 2022. Results Of the 978 studies screened for eligibility, 20 studies were included in the review and were methodologically assessed using the Critical Appraisal Skills Programme. All included studies consistently indicate that participation in a peer led CSHG leads to multiple perceived benefits, that is, informational support, shared experience, learning from others, helping others as well as cultivating humour as a coping strategy. Additionally, various challenges in CSHGs were identified, that is, confrontation with the suffering of others, divergent information needs, distressing group dynamics and challenging aspects concerning leadership and sustainability. Conclusion This indicates that groups need low‐threshold offers to be able to organise support in case of need.